Nano-scale heterogeneity-driven metastability engineering in ferrous medium-entropy alloy induced by additive manufacturing. (December 2021) - Park, Jeong Min; Asghari-Rad, Peyman; Zargaran, Alireza; Bae, Jae Wung; Moon, Jongun; Kwon, Hyeonseok; Choe, Jungho; Yang, Sangsun; Yu, Ji-Hun; Kim, Hyoung Seop
Abstract: Selective laser melting (SLM) offers unprecedented advantages in fabrication of metals and alloys with complex geometry and unique microstructural features with hierarchical heterogeneity. The SLM process also induces a unique cell structure with high dislocation density and solute segregation at cell boundaries. Here, we propose an innovative utilization of unique dislocation network to achieve superior mechanical properties through metastability engineering of ferrous-medium entropy alloy (FeMEA). While the high dislocation density at cell boundaries contributes to the improvement of yield strength as additional barriers of dislocation movement, the solute segregation at cell boundaries can beneficially control the phase instability of matrix in materials produced by SLM. Our results demonstrate that solute segregation at cell boundaries decreases the face-centered cubic phase stability in the matrix and activates transition of the deformation mechanism from slip to metastable plasticity (i.e., transformation-induced plasticity). Furthermore, the high density of dislocation at cell boundaries also has an effect on not only yield strength enhancement but also controlling kinetics of metastable plasticity, and it beneficially contributes the high ductility of the SLM-processed FeMEA. This work presents a new microstructural design strategy for beneficially customizing the material performance of high-quality products based on SLM-driven metastability engineering of metallic materials. Graphical abstract: Image, graphical abstract